DEFINING TESTS OF HEAT-RESISTANT YTTRIUM-CONTAINING SEALING COATINGS FOR HIGH-TEMPERATURE GAS-EROSION RESISTANCE - Kubich, Vadym; Fasol, Yelyzaveta (Problems of Friction and Wear, 2023)
This article describes the testing of heat-resistant yttrium-containing sealing coatings for high-temperature gas-erosion resistance. The study includes careful visualization and characterization of the geometry of the cut-in profile, observation of changes in surface color, and analysis of the internal structure of powder coatings. The first important conclusion is that there are no obvious changes in the geometry of the flute profile and the configuration of the edges, bottom and sides. This indicates the absence of significant mechanical wear of the surface of the coating materials under the influence of high-temperature gas flow. Further analysis suggests that the modeled mechanical pressure and velocity of the flare jet were not large enough to cause destruction of the coating surfaces. A noticeable change in the color of the surfaces was noted. This phenomenon may be the result of the formation of oxides on the surface of materials under the influence of elevated temperature. The exact chemical composition and nature of these oxides require further research to fully understand. Studies indicate the presence of deformation of the internal structure of powder coatings, as well as the accumulation of zones with high and low microstresses. These phenomena indicate the possibility of micro-wear of the coating materials and the formation of additional cohesive bonds. it was found that the yttrium content affects the rate of mass gain of coatings. The weight gain depends on the yttrium concentration and the method of coating application. This relation can have important practical applications in the development of tribological materials with improved properties.